INDEX OF SCIENTIFIC REVIEWERS, LANKESTERIANA VOL. 21–22, 2021–2022 - International Journal on Orchidology, Lankesteriana (Universidad de Costa Rica, 2022)
The Editor-in-Chief, Managing Editors, Editorial Committee, Editorial Board, and Editorial staff of LANKESTERIANA acknowledge the reviewers listed below for their willing cooperation. It is greatly appreciated that they have generously invested their time and competence in providing valuable comments and advice, for the benefit of the authors, the editorial staff, and the readers of LANKESTERIANA